Design and Effectiveness of Text-, Visual-, and Audio-Oriented Multimedia Based on E-Learning for User Experience in Museums - Hasdianto, Tri; Sugiarta, Nugraha (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Museum management can no longer rely on traditional archiving methods due to the dynamic development of media. A new approach is needed through digital archiving presented via interactive multimedia devices, enabling information to be delivered quickly, easily, and engagingly. The main challenge lies in ensuring the effectiveness of information delivery so that content is thoroughly understood by visitors. This study was conducted at Bale Panyawangan Diorama Purwakarta (BPDP) and Bale Panyawangan Diorama Nusantara (BPDN), employing an e-learning approach to assess the effectiveness of information delivery and a user experience (UX) framework to evaluate the quality of user interaction. The research process was carried out under conditions where the museums were deliberately arranged to be free from other visitors, in collaboration with the museum management, allowing the trials to run more focused and controlled. The findings indicate that visual multimedia formats were the most effective in delivering information, while text-based formats scored the lowest. These results highlight the significant role of pragmatic UX quality in enhancing information reception. Building on these findings, the study also proposes a follow-up design in the form of a wall projection (hyperwall) as an alternative to touchscreen devices to strengthen interactivity. The outcomes of this research and design provide a foundation for future multimedia development in museums.